Pergeseran Bahasa Jawa Ngoko dalam Komunitas Transmigrasi Desa Mukti Makmur Kota Subulussalam : Pergeseran Bahasa - Eni Sudarwati; Emilda; Iba Harliyana (Global Action and Education for Society, 2026)
This study aims to describe the process of ngoko Javanese language shift and identify the factors causing the shift in ngoko Javanese language in the community of Mukti Makmur Village, Simpang Kiri District, Subulussalam City. This study is a qualitative descriptive study. The data collection techniques for this study used observation techniques, structured interviews, recording techniques, and note-taking techniques. Based on the results of the study, it shows the process of ngoko Javanese language shift and the factors causing language shift in the community of Mukti Makmur Village, there are 40 data in total, namely 20 data related to language shift and 20 data related to language shift factors. After analyzing the research data, it was found that the language shift process is subordinate bilingual (B1-B2) consisting of 6 informants, equivalent bilingual (B1 = B2) 1 informant, subordinate bilingual (B2-B1) as many as 10 informants and monolingual (B2) as many as 3 informants. Then, there are language shift factors as many as 1 informant due to migration factors, 7 informants due to education factors, and 12 informants due to demographic factors. This language shift is most pronounced among the younger generation, who prefer to use Indonesian, both within the family and in society.